PENJERNIHAN SIRUP PALA DENGAN CHITOSAN DAN HEMISELLULASE - Nanan Nurdjannah Dept. TIN (Jurnal Teknologi Industri Pertanian, 2006)
ABSTRACT        Indonesia is the main producing country for nutmeg ( 70-75 % ), followed by Grenada (20 – 25 %). The nutmeg production in 2001 to 2003 are 23,575; 23,112 and 23,279 tonnes respectively. Commercial processing which is done recently is to produce nutmeg oil, nutmeg seed with and whithout shell, and fuly. Most of the above products are to be exported. Nutmeg pericarp about 83.3 % of the whole nutmeg fruit has not been used effectively, in the contrary it can cause environmental problem. Nutmeg pericarp has nice specific flavor, contain vitamins and minerals such as calcium, phosphor and vitamin C. Because of its specific characteristics and component, it could be used to produce a few kind of foods and beverages such as sweets, jam, syrup and jelly. Improving the use of nutmeg pericarp by diversification of the product, it is hoped it could improve the farmer income, create job opportunity and protect the enviromental. The nutmeg syrup which has been produced nowadays  has poor appearance because of its high turbidity. The clarification of the syrup which has been done is to let it floculated  by it self, and the process take quite a while. To solve the above problem the use of chitosan and hemicellulase was studied to clarify syrup solution . The treatment applied consists of 0.5% chitosan, 0.7; 0,8 and 0,9% hemicellulase, 1; 2 and 3 hours incubation time (on 300C). The experiment was arranged as Completely Randomized Design, factorially with 2 replication. The result showed that the treatment combination of chitosan and hemicellulase could clarify the syrup very promisingly. The hemicellulase consentration and incubation time influenced the syrup turbidity and other characteristics. The optimum treatment which produced low turbidity syrup (clear syrup) with high value of color, taste and flavor was 0,5 % chitosan, 0.9% hemicellulase consentration with 3 hours incubation time. Keyword : nutmeg syrup, clarification, chitosan, hemicellulose, vitamin C